Immediacy and fact-checking: analysis from the Ecuador Chequea portal - Vélez Bermello, Gabriela Lourdes (2020)
Fake news and disinformation have long been the subject of debate in the media. These are engulfed by the immediate in the process of construction of reality and interests, to point out some of the conditions that the system generates. The Internet acts as a “double-edged sword”; on the one hand, a great avalanche of information is evident and, on the other, the lack of credibility in the news portals. For this reason, the practice of data verification is positioning itself, although with divergent methodologies and techniques. This research proposes a status of the studies generated in relation to the fact-check, to then offer an analysis of the periodicity of contents that are published on the Ecuador Chequea web portal, inquiring into the different sources used by the checking team, in order to classify whether or not the information is true. With the support of theoretical bases and applying systematic observation, this work contributes to the reflections on the treatment of news in the first information verification portal in Ecuador.